The Essence and Structure of the Analysis of International Order - Pietraś, Marek (Roczniki Nauk Społecznych, 2024)
International order is a category of analysis of international relations at the level of the international system. It is therefore a category of ontology, but also of the epistemology of these relations. As a category of ontology, it is a dynamic process specified by the specific conditions of a given historical moment. The aim of the article is – firstly – to propose an understanding of the essence of international order. A neutral understanding of it has been proposed, considering that it is a way of organizing and functioning of the international system at a given moment. Secondly, an important goal is to propose a structure of analysis of international order, considering that it is necessary to take into account: 1) the polarity of the international system, 2) political values, 3) norms, 4) institutions – organizations. A new model of understanding polarity is proposed. First, instead of exclusively structural thinking with a focus on the structure of power concentration (bipolar, multipolar, etc.), a structural-functional approach is proposed, taking into account the concentration of power and the strategy of its application. Second, the analysis of polarity only at the level of the global international system does not reflect the complexity of this phenomenon, when the importance of regional powers increases. It is proposed to analyze polarity as a two-level phenomenon, taking into account the level of the global system and global powers and the level of regional systems and regional powers.